History and Justice: on the political uses of the past - Terra Dall’Agnol, Rafael (2020)
This brief essay aims to understand how the relationship between History and Justice, the historian and the judge, arises from debates, sometimes controversial, that occurred around the Holocaust. Using as a reference the discussions that took place in France and Germany, this essay is based mainly on the judicial process involving the writer David Irving and the historian Deborah Lipstadt. In the final part of this work, the films Denial (2016) and Judgment at Nuremberg (1961), are referred to as examples of cinema's ability to demonstrate how history is mobilized in the courts.